2012
DOI: 10.1108/10662241211250980
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of information retweeting in microblogging

Abstract: Purpose -The purpose of this paper is to propose a conceptual model to investigate the determinants of information retweeting in microblogging based on Heuristic-Systematic Model. Design/methodology/approach -Microblogging data about emergency events from Sina microblogging (http://weibo.com) are collected and analyzed with text mining technology. The proposed hypotheses are tested with logistic and multiple linear regressions. Findings -The results show that source trustworthiness, source expertise, source at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
138
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(145 citation statements)
references
References 38 publications
6
138
0
1
Order By: Relevance
“…Yan, Yi, and Wu (2012) studied user behavior on maicroblog site, and found user interest and social identity have impact on comments and retweeting. Liu, Liu, and Li (2012) found that source trustworthiness, source expertise, source attractiveness, and the number of multimedia have significant effects on the information retweeting. Guan, Gao, and Yang (2014) found that male users are more likely to be involved in hot events, and messages that contain pictures and those posted by verified users are more likely to be retweet, while those with URLs are less likely.…”
Section: Literature Reviewmentioning
confidence: 98%
See 1 more Smart Citation
“…Yan, Yi, and Wu (2012) studied user behavior on maicroblog site, and found user interest and social identity have impact on comments and retweeting. Liu, Liu, and Li (2012) found that source trustworthiness, source expertise, source attractiveness, and the number of multimedia have significant effects on the information retweeting. Guan, Gao, and Yang (2014) found that male users are more likely to be involved in hot events, and messages that contain pictures and those posted by verified users are more likely to be retweet, while those with URLs are less likely.…”
Section: Literature Reviewmentioning
confidence: 98%
“…The x t in the formulae (2.1) is calculated as: Liu et al (2012) and Guan et al (2014) measure microblog attraction with retweeting times. Lun et al (2014) use numbers of comments to measure microblog attraction.…”
Section: Data Collectionmentioning
confidence: 99%
“…Specifically, we assume that the company's relational outcomes on social media is a result of the message characteristics immediately apparent during the interaction (content features) andon a higher structural level -of a company's overall social media management strategy and the manageable account characteristics. While some related social media analytics research has been conducted on the content and context aspects [e.g., 66,105], there is a need for more research on the strategic use of social media by companies [5]. For instance, recent findings demonstrate the general effectiveness of corporate social media engagement on relational outcomes [22] or provide some advice regarding the communicative behavior of company employees to increase sales [35].…”
Section: Theoretical Backgroundmentioning
confidence: 96%
“…To date, a large number of studies have been conducted on predicting the retweetability of each tweet from macro perspectives or large-scale analytics with methodological bases of content analysis and social network analysis [14]. For example, Suh et al [10] found that the number of URLs and hashtags in According to Statistics, it is estimated that there were more than 7 million Twitter users in South Korea in 2013 [15].…”
Section: Introductionmentioning
confidence: 99%